2017
DOI: 10.1177/0142723717691087
|View full text |Cite
|
Sign up to set email alerts
|

Lexical, morphological and syntactic development in toddlers between 16 and 30 months old: A comparison across European Portuguese and Galician

Abstract: The main aims of this study were to investigate the relationship between the lexical size and the emergence of morphological and syntactic markers in toddlers between the ages of 16 and 30 months and to compare these results between Galician and European Portuguese. Parents of 3012 Portuguese toddlers and those of 1081 Galician toddlers completed the MacArthur-Bates Communicative Development Inventory: Words and Sentences. The results indicated that the number of words, the ability to combine words and the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…One of the first markers of grammar development is the ability to combine words. Studies using parental reports indicate that approximately 50% of children already combine words by approximately ages 1;5 to1;7, and nearly all children combine words by the age of 2;0 (Simonsen, Kristoffersen, Bleses, Wehberg, & Jorgensen, 2014; Trudeau & Sutton, 2011;Viana, Pérez-Pereira, et al, 2017). After starting to combine words, children produce sentences which are progressively longer and more complex.…”
Section: Vocabulary and Grammar Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first markers of grammar development is the ability to combine words. Studies using parental reports indicate that approximately 50% of children already combine words by approximately ages 1;5 to1;7, and nearly all children combine words by the age of 2;0 (Simonsen, Kristoffersen, Bleses, Wehberg, & Jorgensen, 2014; Trudeau & Sutton, 2011;Viana, Pérez-Pereira, et al, 2017). After starting to combine words, children produce sentences which are progressively longer and more complex.…”
Section: Vocabulary and Grammar Developmentmentioning
confidence: 99%
“…Studies have consistently indicated that vocabulary is a strong predictor of grammar development (Bates & Goodman, 1997, 1999Devescovi et al, 2005). Studies using different versions of the CDI indicate that word combination is already observable in certain toddlers with a 50-100-word lexicon and that more than 90% of toddlers produced word combinations at the 300-word level (Fenson et al, 1994;Viana, Pérez-Pereira, et al, 2017). These findings show the inter-relatedness of lexical and syntactic growth: toddlers start to produce longer and grammatically more complex sentences as their lexicon size increases.…”
Section: Predictors Of Vocabulary and Grammar Growthmentioning
confidence: 99%
“…Lexical composition changes with vocabulary growth and the emergence of grammar (Bates et al, 1994;Caselli et al, 1995;Kauschke & Hofmeister, 2002;Ogura et al, 2006;Trudeau & Sutton, 2011). A high interdependence between lexical and grammatical skills across a variety of languages has been reported in previous studies (Caselli, Casadio, & Bates, 1999;Chi, 2002;Dixon & Marchman, 2007;Trudeau & Sutton, 2011;Viana, Pérez-Pereira, Cadime, Silva, Santos, & Ribeiro, 2017). Trudeau and Sutton (2011) investigated expressive vocabulary and early grammar of 16-to 30-month-old children using parental reports.…”
Section: Possible Influencing Factors Of Lexical Compositionmentioning
confidence: 86%
“…For example, the English form includes the complexity of the child's multi-word utterances (Fenson et al, 2007), and the Finnish form includes the child's usage of inflections (Lyytinen, 1999). The CDI-LF has been adapted for numerous languages (for a comparison study, see Bleses et al, 2008) and used widely (e.g., Fenson et al, 1993;Marchman and Martine-Sussmann, 2002;Stolt et al, 2009;Torppa et al, 2010;Eriksson et al, 2012;Simonsen et al, 2014;Marjanovič-Umek et al, 2017;Viana et al, 2017;Pérez-Pereira and Cruz, 2018;Cadime et al, 2019;Patrucco-Nanchen et al, 2019). As a result, there is plenty of evidence of the validity and usability of different languages in longitudinal studies (Fenson et al, 2007;Hurtado et al, 2014;Jago et al, 2023).…”
Section: Introductionmentioning
confidence: 99%